Relationship of Prayer With Mental Health - Dadang Herdiansyah; Sri Ramadhan; Muhammad Farid; Andriyani Asmuni; Masyitoh Masyitoh; Ernyasih Ernyasih; Abul A’la Al Maududi; Dihartawan Dihartawan (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The increase in the population in Indonesia experiencing mental disorders is getting sharper. In Islam, more worship will promote good mental health. This research uses library research methods. Based on the results of literature research shows that someone who always performs prayer can overcome the problems of life that are being experienced so tends to have good mental health. The implementation of worship in the context of Islam such as the implementation of prayers, remembrance, reading the Qur'an, and other worship, can be a way to get mental health.